An enantioselective three-component reaction of diazoacetates with indoles and enals by iridium/iminium co-catalysis. Issue 13 (13th January 2016) - Li, Mingfeng; Guo, Xin; Jin, Weifeng; Zheng, Qing; Liu, Shunying; Hu, Wenhao
Abstract : The first example of chiral secondary amine and iridium(i ) co-catalyzed enantioselective three-component reaction of aryldiazoacetates, indoles and enals was rationally designed and developed to afford 3-substituted indoles in good yields and with excellent enantioselectivity. Abstract : The first example of chiral secondary amine and iridium(i ) co-catalyzed enantioselective three-component reaction of aryldiazoacetates, indoles and enals was rationally designed and developed to afford 3-substituted indole derivatives in good yields and with moderate diastereoselectivity as well as excellent enantioselectivity. This reaction is proposed to proceed through the enantioselective trapping of iridium(i )-associated zwitterionic intermediates via selective 1, 4-addtition to the chiral amine activated enals.